EKSISTENSI ‘URF SEBAGAI SUMBER PELEMBAGAAN HUKUM NASIONAL - M, Sirajuddin M (Madania: Jurnal Kajian Keislaman, 2015)
The Existence of ‘Urf as Resource of National Law Institution. The Academic proposition of this studyaims at describing how the existence of ‘urf (living law) that shares the contributions in the national law, andthat incorporates norms of Islamic law which are essential part of the resource development of national laws.Theoretical framework that has been highlighted is the theory of ‘urf sahih and‘urf fasid, whereas the method ofthis study is the study of literature related to this theme. The result of the study seemed up as the existence oflegal norms that live in the community should be an essential part of national development. The developmentof national law should not be out of the sign of legal principle theory of living law because it proved that it iscapable of delivering Indonesia into the front gate of Independence and formulating universal values in the lifeof the nation. Hence, norms of Islamic law with the law of development theory should take into considerationthe living law as it has contributed to the inclusive development and dynamic law. Process of integrating thevalues of Islamic law in the national legal system will containinly work well as such effect has already producedby a number of laws and regulations that contains nuances of Islamic law